2015
DOI: 10.1116/1.4921198
|View full text |Cite
|
Sign up to set email alerts
|

Resputtering effect during MgO buffer layer deposition by magnetron sputtering for superconducting coated conductors

Abstract: In this study, MgO thin films were deposited by radio-frequency magnetron sputtering. The film thickness in the deposition area directly facing the target center obviously decreased compared with that in other areas. This reduction in thickness could be attributed to the resputtering effect resulting from bombardment by energetic particles mainly comprising oxygen atoms and negative oxygen ions. The influences of deposition position and sputtering pressure on the deposition rate were investigated. Resputtering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It was also found that the average EMSE showed some variations after Ag/FC sputtering. The variations were due to the occurrence of possible resputtering phenomena during the FC sputtering [21]. The resputtering phenomenon of Ag particles was resulted from the bombardment of energetic particles mainly comprising fluorine (F) atoms and negative fluorine (F − ) in this experiment.…”
Section: Resultsmentioning
confidence: 96%
“…It was also found that the average EMSE showed some variations after Ag/FC sputtering. The variations were due to the occurrence of possible resputtering phenomena during the FC sputtering [21]. The resputtering phenomenon of Ag particles was resulted from the bombardment of energetic particles mainly comprising fluorine (F) atoms and negative fluorine (F − ) in this experiment.…”
Section: Resultsmentioning
confidence: 96%
“…Ion bombardment can lead to textural changes and the latter is also valid for NOI bombardment. For example, NOIs seem to control the the film texture of MgO thin films deposited by RF magnetron sputtering [195,196]. Textural changes as function of the reactive gas flow are also often observed during reactive sputtering when the target state changes from metallic to poisoned.…”
Section: Film Texturementioning
confidence: 99%
“…Barabasi et al [44] summarised the fractal characteristics during surface growth. Silver thin films with silicon substrates are prepared using a radio frequency magnetron sputtering system; this process is similar to the fabrication of CeO 2 /YSZ buffer layer by Zhang et al [45] and the deposition of MgO buffer layer by Xiao et al [46]. During the coating process, the working power is 100 W, the coating time is 12 min, and the substrate temperature is 300 • C. The surface morphologies of the silver thin film measured by AFM (tapping mode) at L of 1 µm are illustrated in Figure 2.…”
Section: Surfaces Of a Silver Thin Filmmentioning
confidence: 99%